Ahead of the Curve: Responses From Patients in Treatment for Obsessive-Compulsive Disorder to Coronavirus Disease 2019 - Kuckertz, Jennie M.; Van Kirk, Nathaniel; Alperovitz, David; Nota, Jacob A.; Falkenstein, Martha J.; Schreck, Meghan; Krompinger, Jason W. (Frontiers in Psychology, 2020)
Alongside concern about the physical health impacts of the coronavirus disease 2019 (COVID-19) crisis, public health officials have also raised concerns about the potential for massive mental health impact. This has led many to wonder, how are individuals with obsessive-compulsive disorder (OCD) and especially those with contamination fears doing in the era of COVID-19? We present data from eight patients in our residential treatment program for OCD and related disorders who were admitted prior to any COVID-19 restrictions and continued in treatment at the facility during the pandemic. Much like the general population, our patients varied in the ways they were impacted by COVID-19, yet the majority experienced improvements in OCD symptoms despite the context. This is not to downplay the many ways in which our patients were personally affected by COVID-19. Rather our patients’ relatively resilient responses mirror our program’s treatment model, which emphasizes exposure and response prevention within the complementary framework of acceptance and commitment therapy. The intention of this article is to challenge the notion that by definition this population will fare worse than the general public or that exposure and response prevention cannot proceed effectively during this time. In contrast, we underscore that effective OCD treatment can and should continue in the era of COVID-19.